2000
DOI: 10.1016/s0928-8244(00)00157-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of chemotaxis, O2− production and myeloperoxidase release from human polymorphonuclear leukocytes by the ornithine-containing lipid and the serineglycine-containing lipid of Flavobacterium

Abstract: The ornithine-containing lipid (OL) and the serineglycine-containing lipid (SGL) of Flavobacterium activated and modulated the functions of human polymorphonuclear leukocytes (PMNs). The OL and the SGL strongly activated fMet-Leu-Phe- and interleukin-8-induced chemotaxis of PMNs at the concentration of 0.1 microg ml(-1), and a synthetic OL also activated the function of PMNs. Further, the OL strongly activated O(2)(-) production from PMNs. Although the OL and the SGL slightly modulated myeloperoxidase release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…However, lipids containing lysine or serine amino acids, or serine-glycine dipeptides, with analogous backbone structures to OL have previously been observed in Agrobacterium tumefaciens [18] and Flavobacterium meningosepticum [19]. Unfortunately, little detail regarding the molecular structures of OL in R. sphaeroides is available, with prior work limited to their identification based on their migration position on TLC plates using ninhydrin (amino-positive) and molybdate (phosphate-negative) spray results [6,16,17].…”
Section: Introductionmentioning
confidence: 98%
“…However, lipids containing lysine or serine amino acids, or serine-glycine dipeptides, with analogous backbone structures to OL have previously been observed in Agrobacterium tumefaciens [18] and Flavobacterium meningosepticum [19]. Unfortunately, little detail regarding the molecular structures of OL in R. sphaeroides is available, with prior work limited to their identification based on their migration position on TLC plates using ninhydrin (amino-positive) and molybdate (phosphate-negative) spray results [6,16,17].…”
Section: Introductionmentioning
confidence: 98%
“…Several mechanisms that protect Flavobacterium spp. from ROS, such as superoxide dismutase (SOD) and catalase activity have been described previously (Sanchez-Moreno et al 1989, Kawai et al 2000, Nematollahi et al 2003. The presence or enhanced expression of one of these mechanisms in the highly virulent strain may account for higher resistance to killing by ROS.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously demonstrated that neutrophilic enzymatic activity is enhanced by stimulation with FMLP and proinflammatory cytokines. MPO was believed to exist not on the surface but inside neutrophils and seemed to leak MPO and other lysosomal peroxidase from the granules when neutrophils were activated (24). However, no direct evidence was observed to leak MPO on the neutrophil surface during neutrophil activation, whereas expression of PR3 on the surface of the primed neutrophils can be detected (4,13,50).…”
Section: Discussionmentioning
confidence: 99%